The Impact of Leadership Style and Work Motivation on Employee Performance at Kanyoho Car Workshop - Afrizal; Akmal; Chaidir; Marzuki; Zakaria (Proceeding of International Conference on Multidisciplinary Research, 2024)
This study aims to examine the impact of leadership style and work motivation on employee performance at Kanyoho Car Workshop in Banda Aceh. The population of this research includes 9 respondents, comprising 1 owner and 8 employees of Kanyoho Car Workshop. The sample size is 8 individuals, excluding the owner. The data analysis model employed is multiple linear regression, with independent variables consisting of leadership style and motivation, and the dependent variable being employee performance. Data collection techniques involve documentation and questionnaires, incorporating a set of statements and written questions provided to respondents for completion based on their actual circumstances. The research findings reveal a robust and positive correlation between leadership style and motivation with the performance of Kanyoho Car Workshop employees. Other variables, such as work discipline, compensation, job stress, and others, collectively contribute to 37.2% of the observed variance. Recommendations include the necessity for enhancing leadership style among employees, as it significantly influences employee performance. Moreover, recognition and rewards are crucial to fostering motivation in the workplace